Curcumin reduces inflammation process in mice model preeclampsia - Rahardjo, Bambang; Widyalaksono, Agung; Baihaqi, Irfani (Majalah Obstetri & Ginekologi, 2025)
HIGHLIGHTS Increased oxidative stress results in increased iNOS in pre-eclampsia. COX-2 expression in the placenta of women suffering from preeclampsia increases and is associated with increased thromboxane production.   ABSTRACT Objective: Preeclampsia is one of the most frequently documented pregnancy complications, with a prevalence of approximately 2 to 15% of all pregnancies. Preeclampsia is a leading cause of maternal mortality. According to research in Indonesia, preeclampsia accounts for 66.8% of all cases of hypertension during pregnancy. This research aims to evaluate the impact of curcumin on serum levels of COX-2 and iNOS in a mouse model of preeclampsia. Materials and Methods: This study employed a true experimental design with a post-test-only controlled group approach using pregnant Rattus norvegicus as a preeclampsia model. Curcumin was administered orally via a feeding tube after dissolving powdered tablets. Dosages were 30 mg/day, 50 mg/day, or 100 mg/day, adjusted for the rats' weight. Serum COX-2 and iNOS levels were measured using ELISA kits from Bioassay Technology Laboratory, with concentrations reported in pg/ml. Analysis was performed using SPSS for Windows 19.0. Results: Serum COX-2 levels showed significant differences (p < 0.05) across groups. L-NAME treatment increased COX-2 levels compared to the negative control. Curcumin (50 and 100 mg/kgBW) reduced COX-2 levels significantly compared to the positive control, with no notable differences between curcumin doses. For iNOS levels, significant differences were also found (p < 0.05). Curcumin at 100 mg/kgBW significantly lowered iNOS levels compared to the positive control, with no significant differences between other treatment groups. Conclusion: Curcumin administration effectively reduces COX-2 and iNOS levels in the serum of Rattus norvegicus with a preeclampsia model.